2013
DOI: 10.12948/issn14531305/17.4.2013.02
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Usage of Social Networking Websites: Perceptions and Opinions of Romanian University Students

Abstract: As social network sites (SNWs) have been shown to connect individuals to people with whom they have a previously established offline connection [9], as well as to connections of different degrees of relational closeness [5], it is likely that people turn to SNWs as an efficient way to tap these connections for information-seeking purposes. These sites can be oriented towards workrelated contexts (e.g., LinkedIn.com), roman-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
(10 reference statements)
1
4
0
Order By: Relevance
“…Very less number of students were satisfied with the other SMNSs. The results were somewhat consistent with the studies of Hall 13 , et al, and Iordache and Lamanauskas 14 . Figure 3 depicted the results that the majority of 61.24 per cent students preferred to make their profile visible only for people whom they knew well.…”
Section: Use and Satisfactionsupporting
confidence: 91%
“…Very less number of students were satisfied with the other SMNSs. The results were somewhat consistent with the studies of Hall 13 , et al, and Iordache and Lamanauskas 14 . Figure 3 depicted the results that the majority of 61.24 per cent students preferred to make their profile visible only for people whom they knew well.…”
Section: Use and Satisfactionsupporting
confidence: 91%
“…(Kitsantas et al, 2016;Sendurur et al, 2015). Regarding the issue, Iordache and Lamanauskas (2013) asked university students to evaluate the functions of SNSs in order of their importance. The students evaluated and ranked these functions as (1) communication, (2) learning and exchanging information, (3) exchanging the items such as photos and videos and (4) friend search.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in a study conducted by Iordache and Lamanauskas (2013), the most important functions of SNSs for Romanian students were communication, learning and exchanging information, exchanging photos and videos, friend search and messaging. Jieun and Richardson (2016) found that students used SNSs frequently and actively for various reasons in their daily life, and they showed positive perceptions of using SNSs for educational purposes.…”
Section: Why Do Distance Education Students Use Snss?mentioning
confidence: 95%